Human papillomavirus tumour status is not associated with a positive depression screen for patients with oropharyngeal cancer. Issue 9 (19th July 2017) - Qualliotine, J R; Califano, J A; Li, R J; Gold, D; Messing, B; Lee, G; Ha, P; Fakhry, C
Abstract: Background: Several risk factors for depression in patients with oropharyngeal cancer have been determined. However, it is unknown whether human papillomavirus associated oropharyngeal cancer, which has a distinct clinico-demographic profile, modulates this risk. Methods: A retrospective analysis was conducted of patients with oropharyngeal cancer. These patients had completed a 10-item depression screening questionnaire before receiving treatment for their disease from 2011 to 2014. Associations between patient or disease characteristics and depression screening questionnaire results were investigated. Results: The study comprised 69 patients, 31 (44.9 per cent) of whom screened positive for depression. There were no significant differences in distributions of clinico-demographic or histopathological characteristics, including human papillomavirus tumour status, by depression screen result. Conclusion: This population has a high risk for depression, but no obvious risk factors, including human papillomavirus tumour status, were associated with an elevated risk. This inability to risk-stratify patients by clinico-demographic or disease characteristics emphasises the importance of regular depression screening for all patients in this population.